AGE AND GENDER RELATED OUTCOMES IN PATIENTS UNDERGOING HEAD UP TILT TEST FOR VASOVAGAL SYNCOPE - Asad, Muhammad; Khan, Kashif; Nazir, Muhammad Talha Bin; Ali, Muhammad; Nazir, Atif; Khan, Hamid Sharif; Khan, Aleena; Khan, Shanzah; Khan, Qurban Hussain (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate different types of vasovagal syncope among the study group and assess the various outcomes in relation to age and gender in patients.Study Design: Cross sectional study.Place and Duration of Study: Electrophysiology department, Rawalpindi Institute of Cardiology, Rawalpindi Pakistan, from July to Dec 2020.Methodology: We analyzed prospectively 260 patients after excluding patients not meeting inclusion criteria to undergo HUTT. One hundred and two patients who were finally diagnosed vasovagal were included. Italian protocol was used and nitroglycerin was given for induction. Different responses were noted and outcome and hemodynamic parameters were compared according to age and gender. The collected data was analyzed by using SPSS-23.Results: Out of 102 patients, 57 (55.9%) were males and 45 (44.1%) were females with the mean age of 41.95 ± 18.91 years. Common prodromal symptoms were dizziness 27 (26.5%), vertigo 27 (26.5%), blackout 25 (24.5%) and apprehension 16 (15.7%). Mixed response was common in males while for females it was vasodepressor. Distribution of different responses and hemodynamic parameters were not statistically significant among age groups.Conclusion: Dizziness and vertigo are the important prodromal symptoms. Older age group and females are more likely to have vasodepressor response but there is no difference in the SBP, DBP and HR parameters among both genders. Nitroglycerin is a useful drug for reaching to the diagnosis.